A feasibility study of SMART reactor power performance optimizations-part 1: Steady-state and burn-up analysis - Zhong, Yiming; Norman, Paul; Wu, Wenbin (Frontiers in Energy Research, 2022)
SMART is an integral small pressurized water nuclear reactor design with a rated power output of 100 MWe from 330 MWth, but it needs a higher power output for the United Kingdom energy market. This study applies Monte Carlo code OpenMC to build a full-core model and innovatively adjust the simulation coefficients to approach the reactor operating conditions. The analysis results point out the reasonable optimization’s technical direction. The model’s sensitivity to ENDF and JEFF nuclear data libraries and spatial division is tested and verified. Then it performs a series of simulations to obtain the core’s neutronic parameters, such as neutron energy and spatial distributions, effective neutron multiplication factor keff and its variation versus depletion. The analysis found that the initially designed core’s keff is 1.22906, and the temperature reactivity defect is 11612 pcm. In 1129 full-power operating days, the keff will decrease to 0.99126, and the reactor depletes 8.524 × 1026235U atoms. However, the outermost fuel assemblies’ 235U depletion rate is lower than 45% in this extended refuelling cycle, and their ending enrichment is higher than 2.4%. That means the fuel economy of the original design’s two-batch refuelling scheme core layout is insufficient. Improving the thermal neutron fluence in these assemblies may optimize the SMART power performance effectively.